Communication strategy for state defence: a case study of Indonesia’s Ministry of Defence - SANTOSO, TOTOK IMAM; Putro, Guntur Eko (Jurnal Studi Komunikasi, 2025)
Currently, strategic communication in supporting national defence policy faces increasingly complex challenges amid geopolitical dynamics, technological developments, and changing patterns of security threats. In reality, coordination between institutions is still a major challenge, especially in ensuring the integration of messages and synergy of cross-sector communication. In addition, the rampant disinformation and digital propaganda also threaten national security and stability, thus requiring strategic efforts to counter negative narratives that can weaken support for defence policies. How is strategic communication designed and implemented by the Ministry of Defence to support national defence policies? The purpose of this study is to analyse and identify the role of strategic communication in supporting the implementation of national defence policies, with a focus on the effectiveness of information delivery, coordination between stakeholders, and mobilisation of public support. The theory used in this research is Strategic Communication Theory developed by Hallahan, Holtzhausen, van Ruler, Verčič, dan Sriramesh 2007. The research method employed is a literature study through reviewing, analysing and synthesising various relevant literature sources. The results generated found that there are several indicators to realise strategic communication in supporting the National Defence policy and that is by integrating communication adaptability, inter-Institutional Coordination, Effectiveness of Communication Channels and Public participation, and involvement so that strategic communication can be an effective tool in strengthening the legitimacy and implementation of national defence policy. The research indicators are communication planning, target audience determination, message framing & narrative development, channel effectiveness, inter-agency coordination, evaluation and feedback mechanism